Needs and preferences for psychological interventions of people with motor neuron disease. Issue 7 (2nd October 2019) - Weeks, Kirsty R.; Gould, Rebecca L.; Mcdermott, Christopher; Lynch, Jessica; Goldstein, Laura H.; Graham, Christopher D.; McCracken, Lance; Serfaty, Marc; Howard, Robert; Al-Chalabi, Ammar; White, David; Bradburn, Mike; et al.
Abstract: Background: There is a lack of knowledge about what factors may impede or facilitate engagement in psychological interventions in people with motor neuron disease (pwMND) and how such interventions can be adapted to best meet the needs of this population. Objectives: To explore the needs and preferences of pwMND with respect to psychological interventions, and how best to adapt such interventions for pwMND. Methods: A series of semi-structured interviews ( n  = 22) and workshops ( n  = 3) were conducted with pwMND ( n  = 15), informal caregivers of pwMND ( n  = 10), and MND healthcare professionals ( n  = 12). These explored preferences and concerns that would need to be considered when delivering a psychological intervention for pwMND. Three areas were explored: (i) perceived factors that may hinder or facilitate pwMND engaging with psychological interventions; (ii) ways in which such interventions could be adapted to meet the individual needs of pwMND; and (iii) views regarding the main psychological issues that would need to be addressed. Workshops and interviews were audio recorded and transcribed and thematic analysis was used to inductively derive themes. Findings: Data could be classified within four overarching themes: unfamiliar territory; a series of losses; variability and difficulty meeting individual needs; and informal support. Conclusions : Flexibility, tailoring interventions to the individual needs of pwMND, and encouraging autonomy are key attributes for psychological interventions with pwMND. Psychological interventions such as Acceptance and Commitment Therapy (ACT) could be acceptable for pwMND if adapted to their specific needs.